Role of Salvia officinal’s Silver Nanoparticles in Attenuating Renal Damage in Rats Exposed to Methotrexate(Part I) - Khudiar, Khalisa Khadhim; Ali Sood, Mustafa (The Iraqi Journal of Veterinary Medicine, 2019)
The aim of the present study was to investigate the protective role of Salvia officinal’s silver nanoparticles as antioxidant on nephrotic damage induced by methotrexate in adult rats. Green silver nanoparticles were synthesized using alcoholic extract of salvia officinal’s leaves, and were characterized by UV-spectrophotometry and scanning electron microscope. The mixing of the plant extract of Salvia. officinal’s with silver nitrate solution (1mM), lead to changing of the reaction mixture color to yellowish within one hour and to dark brown after 8 hours, indicating the generation of Salvia officinal’s silver nanoparticles , due to the reduction of silver metal ions silver (Ag+) into Nano silver particles via the active compounds present in the S. officinal’s plant extracts. Changing in color after the reduction of Ag+ to Salvia officinal’s silver nanoparticles. The reduction rate and formation of nanoparticles can be increased further by increase in incubation time. Silver nitrate conversion to Nano silver particles was found to be successful as suggested by the change in color of the solution to brown. For studying the protective role of Salvia officinal’s silver nanoparticles , twenty eight adult Wister albino rats were randomly assigned and divided in to four groups as follows T1, T2, T3, and T4, They were treated intramuscularly (twice per week) for 45 days as follows; T1:animals in this group, were given Salvia officinal’s (150mg /Kg/.B.W), T2: animals in this groups were given Salvia officinal’s Silver nanoparticles (150mg/Kg B.W.); T3:animals of this groups were given both Methotrexate (0.25mg/kg/ B.W.) and Salvia officinal’s silver nanoparticles (150mg/Kg/B.W); T4: animals in this groups were given methotrexate (0.25mg/Kg B.W.) for 45 days . The animals of all groups were considered as control group at day zero and injected only doubled distilled water Intramuscala. Fasting blood samples were collected at 0, 15, 30 and 45 days of experimental periods from anesthetized rats using retro-orbital sinus technique and cardiac puncture technique, then sera was isolated for measuring: malondialdehyde, glutathione in serum, creatinine, and blood urea nitrogen and uric acid concentrations. The results showed that animals received methotrexate (group T4) caused a case of oxidative stress manifested by significant decrease grower in , elevation in malondialdehyde concentrations, renal dysfunction as documented by significant elevation in serum creatinine, urea and uric acid concentrations. On the other hand, the protective role of salvia officinal’s and Salvia officinal’s silver nanoparticles given concurrently with methotrexate was clarified in groups T2and T3 ,where there was alleviation of renal damage through correction of the previous mentioned parameters and correction of antioxidant status. In conclusion, the current study documented the antioxidant activity and reno protective effects of Salvia officinal’s silver nanoparticles against damaging effects of methotrexate in rats.